Expanding Pharmacist and Student Pharmacist Access to Genetics/Genomics/Pharmacogenomics Competency Education. (March 2019) - Kisor, David F; Farrell, Christopher L
Background: As pharmacogenomics (PGx), a component of genetics/genomics and precision medicine, gains traction in the clinical setting, education of health care providers and health professions students must be made broadly available to improve accessibility of such services to patients. As medication experts with education in pharmacology, pharmacokinetics, and pharmacodynamics, pharmacists must further their education to include pharmacogenomics. Currently, few opportunities exist to gain this type of education, and therefore, these services are not yet broadly available to the public. Objective: The specific goal of this study was to evaluate pharmacists' and student pharmacists' self-assessed perception of competence related to genetics, genomics, and pharmacogenomics as presented via an online "pharmacogenomics certification program" (PGx program). Design: The PGx program was delivered online with the content consisting of 3 background lessons and 8 specific drug-gene lessons presented in the context of pharmacist competency statements. In addition, 11 "video modules" with competency-related PGx content were included to provide a comprehensive program. A pre- and post-course survey instrument was used to evaluate the participants' self-assessed perception of competence related to each of 16 statements. Results: One hundred thirty-seven (137) individuals enrolled in and completed the pharmacogenomics certification program. Overall, participants reported self-perceived improved competency as evidenced by the pre-course survey as compared with the post-course survey for each of the 16 competency statements related to genetics/genomics, including pharmacogenomics. Similar results were observed for the subgroups of student pharmacists (n = 63) and pharmacists (n = 74). Future direction: This study showed that dissemination of genetics/genomics/pharmacogenomics competency statements education can be accomplished via online delivery. This delivery approach can expand genetics/genomics/pharmacogenomics content dissemination. The intent is to reach a broader population of pharmacy students, pharmacists, and other health care providers and health professions students to potentially advance the availability of such services, which can improve the safety and efficacy of medication use for patients.